(untitled) (World Economics and Finance Bulletin, 2022)
The researcher explores the sources of funding, their types in the Iraqi budget and how they are important as a financial tool through which the government can influence economic activity and consequently the standard of living of individuals. When analyzing the current economic situation in Iraq, we see what Iraq is experiencing. We describe it as a complex crisis that is considered the most influential. In recent history, in terms of the spread of the epidemic in nearly 185 countries, the spread of the epidemic is considered to be known par excellence because along with the lack of complete knowledge of dealing with it made it the most influential. On the other hand, the political crisis that preceded the Corona crisis and the economic crisis that followed and the drop in oil prices all put the country in an exceptional circumstance. Yet, the procedures followed by the government are completely opposite to the procedures that must be followed according to the economic stage the country is going through (recession). Also, the number of the poor was (7.300) million, according to 2018 estimates from the Ministry of Planning and Development Cooperation.